Low Pay and Household Poverty - Brian Nolan; Ive Marx (Luxembourg Income Study (LIS), 1999)
Low pay is conventionally measured in terms of the gross earnings of the individual, related to benchmarks derived from the distribution of earnings such as half or two-thirds of the median. Poverty status, on the other hand, is usually assessed on the basis of the disposable income of the household, adjusted for size and composition. The relationship between the two - low pay and poverty - is by no means straightforward, but improving our understanding of it is critical to policy formulation. In this paper we draw on two data sources to investigate what that relationship looks like empirically in industrialized countries: the Luxembourg Income Study database and the European Community Household Panel. The extent of overlap between low pay and poverty is found to be often rather more limited at an aggregate level than might generally be expected, but there is also some variation across countries. These results are based on snapshots from cross-section data, and the importance of a dynamic perspective in this context is emphasized. In conclusion, some of the policy implications are explored.
Keywords: 330; Niedriglohn; Haushaltseinkommen; Armut; EU-Staaten; OECD-Staaten